An application for the Gauss-Bonnet theorem - Gül, Erdal (Pro Mathematica, 1999)
The principal aim of this paper is to give an example of the Gauss-Bonnet Theorem together with its anew structure by using connection and curvature matrices with stereographic projection on the unit 2-sphere, S². We determine an orthonormal basis by applying stereographic projection on S² and we obtain the area of the unit 2 -sphere S² computing connection and curvature matrices.